9
$\begingroup$

Evaluate $$I=\int_{0}^{\frac{\pi}{2}}\frac{dx}{\left(\sqrt{\sin x}+\sqrt{\cos x}\right)^2}$$

My try:

Since $$f(x)=f\left(\frac{\pi}{2}-x\right)$$ we have:

$$I=2\int_{0}^{\frac{\pi}{4}}\frac{dx}{\left(\sqrt{\sin x}+\sqrt{\cos x}\right)^2}$$

Applying $$\int_{a}^{b}f(x)dx=\int_{a}^{b}f(a+b-x)dx$$ we get:

$$I=2 \times 2\int_{0}^{\frac{\pi}{4}}\frac{dx}{\left(\sqrt{\cos x-\sin x}+\sqrt{\cos x+\sin x}\right)^2}$$

$$I=4\int_{0}^{\frac{\pi}{4}}\frac{dx}{2\cos x+2\sqrt{\cos 2x}}$$

$$I=2\int_{0}^{\frac{\pi}{4}}\frac{dx}{\cos x+\sqrt{\cos 2x}}$$

$$I=2\int_{0}^{\frac{\pi}{4}}\frac{\sqrt{\cos 2x}-\cos x}{-\sin^2 x}$$

How to proceed now?

$\endgroup$
  • 2
    $\begingroup$ It is $$\frac{\Gamma \left(\frac{3}{4}\right)^2+4 \Gamma \left(\frac{5}{4}\right)^2}{\sqrt{\pi }}-2$$ $\endgroup$ – Dr. Sonnhard Graubner Feb 23 at 16:03
  • $\begingroup$ How did you calculate that result? It seems to be the correct answer. $\endgroup$ – Peter Foreman Feb 23 at 16:07
  • $\begingroup$ May be question as $\displaystyle I=\int_{0}^{\frac{\pi}{2}}\frac{dx}{\left(\sqrt{\sin x}+\sqrt{\cos x}\right)^4}.$ $\endgroup$ – DXT Feb 23 at 18:43
  • $\begingroup$ BTW: \begin{align}\Gamma\left(\frac54\right)=\frac14\Gamma\left(\frac14\right)\end{align} $\endgroup$ – FDP Feb 23 at 23:41
11
$\begingroup$

\begin{align}I&=\int_{0}^{\frac{\pi}{2}}\frac{dx}{\left(\sqrt{\sin x}+\sqrt{\cos x}\right)^2}\\ &=\int_{0}^{\frac{\pi}{4}}\frac{dx}{\left(\sqrt{\sin x}+\sqrt{\cos x}\right)^2} +\int_{\frac{\pi}{4}}^{\frac{\pi}{2}}\frac{dx}{\left(\sqrt{\sin x}+\sqrt{\cos x}\right)^2}\\\end{align}

In the second integral perform the change of variable $y=\frac{\pi}{2}-x$,

\begin{align}I&=2\int_{0}^{\frac{\pi}{4}}\frac{dx}{\left(\sqrt{\sin x}+\sqrt{\cos x}\right)^2}\\ \end{align}

Perform the change of variable $y=\tan x$,

\begin{align} I&=2\int_{0}^{1}\frac{1}{(1+\sqrt{x})^2\sqrt{1+x^2}}\,dx\\\end{align}

Perform the change of variable $y=\dfrac{1-x}{1+x}$,

\begin{align}I&=\sqrt{2}\int_{0}^{1}\frac{1-\sqrt{1-x^2}}{x^2\sqrt{1+x^2}}\,dx\\ &=-\sqrt{2}\Big[\frac{1-\sqrt{1-x^2}}{x\sqrt{1+x^2}}\Big]_0^1-\sqrt{2}\int_0^1 \frac{\sqrt{1-x^2}-2}{\sqrt{1-x^2}(1+x^2)^{\frac{3}{2}}}\,dx\\ &=-1-\sqrt{2}\int_0^1 \frac{1}{(1+x^2)^{\frac{3}{2}}}\,dx+2\sqrt{2}\int_0^1 \frac{1}{\sqrt{1-x^2}(1+x^2)^{\frac{3}{2}}}\,dx\\ &=-1-\sqrt{2}\left[\frac{x}{\sqrt{1+x^2}}\right]_0^1+2\sqrt{2}\int_0^1 \frac{1}{\sqrt{1-x^2}(1+x^2)^{\frac{3}{2}}}\,dx\\ &=2\sqrt{2}\int_0^1 \frac{1}{\sqrt{1-x^2}(1+x^2)^{\frac{3}{2}}}\,dx-2\\ \end{align}

Perform the change of variable $y=\dfrac{1-x}{1+x}$,

\begin{align}I&=\int_0^1 \frac{x^2+1+2x}{\sqrt{x}(1+x^2)^{\frac32}}\,dx-2\\ &=\int_0^1 \frac{1}{\sqrt{x}\sqrt{1+x^2}}\,dx+2\int_0^1 \frac{\sqrt{x}}{(1+x^2)^{\frac32}}\,dx-2\\ \end{align}

Perform the change of variable $y=\sqrt{x}$ in both integrals,

\begin{align}I&=2\int_0^1 \frac{1}{\sqrt{1+x^4}}\,dx+4\int_0^1 \frac{x^2}{(1+x^4)^{\frac32}}\,dx-2\end{align}

\begin{align}A&=\int_0^1 \frac{1}{\sqrt{1+x^4}}\,dx\end{align}

Perform the change of variable $y=\frac{1}{x}$,

\begin{align}A&=\int_1^\infty \frac{1}{\sqrt{1+x^4}}\,dx=\int_0^\infty \frac{1}{\sqrt{1+x^4}}\,dx-\int_0^1 \frac{1}{\sqrt{1+x^4}}\,dx\\ &=\int_0^\infty \frac{1}{\sqrt{1+x^4}}\,dx-A \end{align}

Therefore,

\begin{align}A&=\frac{1}{2}\int_0^\infty \frac{1}{\sqrt{1+x^4}}\,dx\end{align}

In the same manner one obtains,

\begin{align}\int_0^1 \frac{x^2}{(1+x^4)^{\frac32}}\,dx&=\frac{1}{2}\int_0^\infty \frac{x^2}{(1+x^4)^{\frac32}}\,dx\end{align}

Therefore,

\begin{align}I&=\int_0^\infty \frac{1}{\sqrt{1+x^4}}\,dx+2\int_0^\infty \frac{x^2}{(1+x^4)^{\frac32}}\,dx-2\end{align}

Perform the change of variable $y=x^4$,

\begin{align}I&=\frac{1}{4}\int_0^\infty \frac{x^{-\frac34}}{(1+x)^{\frac12}}\,dx+\frac{1}{2}\int_0^\infty \frac{x^{-\frac14}}{(1+x)^{\frac32}}\,dx-2\\ &=\frac{1}{4}\text{B}\left(\frac{1}{4},\frac{1}{4}\right)+\frac{1}{2}\text{B}\left(\frac{3}{4},\frac{3}{4}\right)-2\\ &=\frac{1}{4}\times \frac{\Gamma^2\left(\frac{1}{4}\right)}{\Gamma\left(\frac{1}{2}\right)}+\frac{1}{2}\times \frac{\Gamma^2\left(\frac{3}{4}\right)}{\Gamma\left(\frac{3}{2}\right)}-2\\ &=\frac{1}{4}\times \frac{\Gamma^2\left(\frac{1}{4}\right)}{\Gamma\left(\frac{1}{2}\right)}+\frac{1}{2}\times \frac{\Gamma^2\left(\frac{3}{4}\right)}{\frac{1}{2}\Gamma\left(\frac{1}{2}\right)}-2\\ &=\frac{1}{4}\times \frac{\Gamma^2\left(\frac{1}{4}\right)}{\Gamma\left(\frac{1}{2}\right)}+\frac{\Gamma^2\left(\frac{3}{4}\right)}{\Gamma\left(\frac{1}{2}\right)}-2\\ \end{align}

It is well known (Euler's reflection formula) that,

\begin{align}\Gamma\left(\frac{1}{2}\right)=\sqrt{\pi}\end{align}

Therefore,

\begin{align}\boxed{I=\frac{\Gamma^2\left(\frac{1}{4}\right)}{4\sqrt{\pi}}+\frac{\Gamma^2\left(\frac{3}{4}\right)}{\sqrt{\pi}}-2}\end{align}

NB:

$\text{B}$ is the Euler beta function.

$\endgroup$
  • $\begingroup$ small correction +1 Perform the change of variable $y=\tan x$, \begin{align} I&=2\int_{0}^{1}\frac{1}{(1+2\sqrt{x}+x)\sqrt{1+x^2}}\,dx\\\end{align} $\endgroup$ – user178256 Feb 24 at 13:11
  • $\begingroup$ You are right. Fixed. Thanks. $\endgroup$ – FDP Feb 24 at 18:22

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.